Enabling Strategies and Policies Toward a Sustainable Environment - Abdul Majeed; Judit Oláh (Energies)
This Topic, Enabling Strategies and Policies toward a Sustainable Environment, addresses the gaps in the literature by synthesizing pioneering research on the mechanisms driving sustainable transitions [...]